Conclusion: The Next Decade and Beyond - Mehmet, Özay; Yorucu, Vedat (Springer, 2020)
Hydrocarbon wealth in the Eastern Mediterranean can become a reality or remain a dream, depending on how far regional energy cooperation can be promoted. We believe reserves discovered so far, and future ones yet to be discovered, may enrich the people of the region, if political leaders opt for rational choices and adapt to the reality of a rapidly emerging world of zero emission cars and cleaner environment while cooperating with neighbours as outlined in our Regional Energy Model. © 2020, Springer Nature Switzerland AG.
Keywords: Energy resources; Eastern Mediterranean; Energy cooperation; Regional energy modeling; Zero emission cars; Energy management